1980
DOI: 10.1007/bf00160740
|View full text |Cite
|
Sign up to set email alerts
|

Erosion by Human Activities in Japan

Abstract: This paper reviews the aspects and the order of magnitude of man's influence upon the [andsurface of japan, with special attention to the recent drastic remodelling and erosion of it induced by urbanization and agricultural activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Grisak & Jackson (1978) emphasized the role of hydraulic conductivity and cation exchange capacity in explaining the subsurface movement of radioactive wastes. Kadomura (1980) showed that the volcanic tephra slopes of Mt. Usu in Hokkaido, Japan, generated sediment yield of about 100 000 m 3 km -2 y-l (1I Bubnov unit = I m 3 km -2 y-l yield, or I mm y-3 ground loss).…”
Section: Background Biogeochemical Cyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…Grisak & Jackson (1978) emphasized the role of hydraulic conductivity and cation exchange capacity in explaining the subsurface movement of radioactive wastes. Kadomura (1980) showed that the volcanic tephra slopes of Mt. Usu in Hokkaido, Japan, generated sediment yield of about 100 000 m 3 km -2 y-l (1I Bubnov unit = I m 3 km -2 y-l yield, or I mm y-3 ground loss).…”
Section: Background Biogeochemical Cyclingmentioning
confidence: 99%
“…Chen (1974), studying the Washington, D.C. and Baltimore regions, was able to make a clear distinction in sediment yields between construction sites and watersheds of urban development (55 km 2 ). Kadomura (1980) has documented the dramatic effects of agriculture and urbanization on sediment yield in Japan. Omernik (1976) found that six categories of land use (forest, mostly forest, mixed, mostly urban, mostly agriculture and agriculture) could be used to give a reasonable explanation of regional nutrient losses in eastern U.S. (Fig.…”
Section: I "°8mentioning
confidence: 99%
“…A good site for collecting evidence of such effects is the widespread bare land in the granite mountains of Japan that was created because of long-term human disturbances (Kadomura, 1980). Throughout Japan's long history, forests have continuously been used to provide basic resources for human activities.…”
Section: Introductionmentioning
confidence: 99%